Seagrass Community Structure at Ratatotok Beach, Southeast Minahasa Regency - Purba, Dhebby; Wagey, Billy; Luasunaung, Alfret; Manembu, Indri; Sumilat, Deiske; Mantiri, Rose (Jurnal Ilmiah Platax, 2023)
The purpose of this research is to know about the type of seagrass, the community structure of seagrass based on the density of type, the density of the relatively, type of frequency, frequency relatively, type of cover, cover relatively, diversity index, dominance and parameter index in surrounding water environment of seagrass at Ratatotok beach. The result of this research is identifying 4 species, namely; Thalassia hemprichii, Enhalus acoroides, Syringodium isoetifolium dan Halodule pinifolia. The value of density is 39 indv/m2, the value type of frequency is 7.9, the value type of cover is 39.15, importance value index had 159.04%. Thalassia hemprichii, diversity index is “medium” with an average value (H’) of 2.63 and a higher importance index with an average value of C of 0.82. Surrounding waters at Ratototok Beach got a “medium” value of seagrass cover value is 39%. Environmental parameters in surrounding waters at Ratatotok beach had a value within; Temperature 31.95 0C, salinity 29.79o/oo, pH 7.62, DO 5.60 mg/L and the type of substrate found is sandy, sandy mud and coral fragments. Keywords: Seagrass, Community structure, Ratatotok beach. Abstrak Tujuan dilakukan penelitian ini yaitu mengetahui jenis lamun, struktur komuntas lamun berdasarkan kepadatan jenis, kepadatan relatif, frekuensi jenis, frekuensi relatif, penutupan jenis, penutupan relatif, indeks keanekaragaman, indeks dominansi dan parameter lingkungan perairan padang lamun yang berada di sekitar Pantai Ratatotok. Hasil yang di peroleh dari penelitian ini teridentifikasi 4 spesies, yaitu: Thalassia hemprichii, Enhalus acoroides, Syringodium isoetifolium dan Halodule pinifolia. Dengan nilai kepadatan 39 ind/m2, frekuensi jenis 7,9, penutupan jenis 39,15, Indeks nilai penting (INP) diperoleh nilai 159,04 %,  pada Thalassia hemprichii, Indeks keanekaragaman “sedang” dengan nilai rata-rata (H’) 2,63 dan indeks dominansi tinggi dengan nilai rata-rata C 0,82. Berdasarkan kategori penutupan lamun yang terdapat di sekitar Perairan Ratatotok dikategorikan “sedang” dengan nilai penutupan 39%. Parameter lingkungan antara lain: suhu 31,95 0C, salinitas 29,79 o/oo, pH 7,62, DO 5,60 mg/l dan jenis substrat yang di temukan adalah berpasir, pasir berlumpur dan pecahan karang. Kata kunci : Lamun, Struktur Komunitas, Pantai Ratatotok